Factors Influencing the Intention to Use Malaysian Dietary Guidelines Among University Students - Sanusi, Ghazari Amri (International Journal of Economics, Management and Accounting, 2020)
The prevalence of obesity, partly due to poor diet and eating behaviors among the population in Malaysia, is on the rise. Not much has been written currently on using the Malaysian Dietary Guidelines (MDG) as a tool for Malaysians to plan an appropriate and balanced diet and to help reduce the risks of obesity and lifestyle-related diseases. Thus, this article seeks to identify the factors influencing intention to use the MDG as a reference for healthy eating among university students in Malaysia. This study is primarily motivated by the fact that university students are known to be in the â€œat-riskâ€ population due to their low-quality diet and poor eating behaviors. Data for this study were collected from a total of 218 university students who participated in a questionnaire survey. To examine a set of hypotheses drawn from the Theory of Planned Behavior, a multiple linear regression method was applied in this study. The results show that attitude (Î² = 0.35; p < 0.01) and subjective norm (Î² = 0.31; p < 0.01) have a direct, positive and significant relationship with intention to use MDG. Contrary to expectations, perceived behavioral control (Î² = -0.08; p > 0.05) was not supported in this study. On closer examination, attitude toward behavior was found to be the more influential predictor of intention to use MDG. The findings from this study provide vital information on factors influencing intention to use MDG, and could serve as a basis by stakeholders, such as policymakers and health professionals, to formulate better and more targeted communication and engagement strategies in dealing with obesity among the university students in Malaysia.